KARAKTERISTIK DAN PERMASALAHAN PABRIK GULA PG X - Farhani, Nuraeni Hadiati; Seno, Petrus Hari Kuncoro; Ramadhani, Annisa Alifa (Ekonomi & Bisnis, 2024)
This research aims to describe the characteristics and problems faced by PG X. Moreover, this research seeks to formulate alternative solutions for PG to give better economics effect for society. This type of research is descriptive qualitative. This research conducted at PG X. The results of this research indicate that PG X is having difficulty of achieving optimal profits. This problems happened because the price of sugar is regulated by the government, while the price of production factors such as fertilizer is free according to market mechanisms. Another problem is that the supply of quality sugar cane is still an obstacle and conditions of inefficiency. The results of this research provide solutions offered for PG (2) production cost efficiency; (3) increasing employee capabilities, and (4) increasing partnerships with farmers that are more intensive, especially in terms of cultivation and post-harvest to improve the quality of sugar cane